2017
DOI: 10.1080/15384101.2017.1371883
|View full text |Cite
|
Sign up to set email alerts
|

Network of phosphatases and HDAC complexes at repressed chromatin

Abstract: Tight regulation of gene expression is achieved by a variety of protein complexes that selectively bind chromatin, modify it and change its transcription competency. Histone acetylases (HATs) and deacetylases (HDACs) play an important role in this process. They can generate transcriptionally active or inactive chromatin through the addition (HATs) or removal (HDACs) of acetyl groups on histones, respectively.Repo-Man is a Protein Phosphatase 1 targeting subunit that accumulates on chromosomes during mitotic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Similar to KRCC1, inhibition of HDAC restores epithelial differentiation and abolishes anchorage independent growth in cancer cells . Genome‐wide binding studies have established a link between PP1 phosphatase and HDAC complexes that bind chromatin regions in an overlapping fashion . Moreover, genome‐wide promoter binding studies in HeLa have identified ~500 promoters that bind PP1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to KRCC1, inhibition of HDAC restores epithelial differentiation and abolishes anchorage independent growth in cancer cells . Genome‐wide binding studies have established a link between PP1 phosphatase and HDAC complexes that bind chromatin regions in an overlapping fashion . Moreover, genome‐wide promoter binding studies in HeLa have identified ~500 promoters that bind PP1 .…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Interestingly like PP1 interacting proteins (PIPs), KRCC1 is intrinsically disordered (Supplementary Figure S8) and specifically associates with the catalytic subunit PP1CC and with HDAC1/2 but not with PP1CA or PP1CB, the other closely related isoforms that are expressed in mammalian cells but differ primarily in their N-and C-termini. 41 While the interaction of PP1CC with HDAC1/2 is well-documented the precise biological implications are emerging 34,35 and suggest regulation of gene transcription 44 and replication stress. 37 Increased acetylation of histone 3/4 and phosphorylation of CHK1 in KRCC1 silenced cells suggest reduced deacetylase and phosphatase activities at these respective sites, which may indicate the inability of PP1CC and HDAC to localize to specific chromatin loci in the absence of KRCC1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We tested this hypothesis by analyzing protein interactions of GFP-SET or GFP by immunoprecipitation experiments using the anti-GFP antibody, followed by mass spectrometry (MS) analysis of the immunoprecipitated proteins. This experimental approach identified SAP18 as an interactor of SET, a component of the mSin3 and histone deacetylase complex 48 , 49 that cooperates with Sufu to repress Gli1-mediated transcription 45 , 46 . The MS analysis also revealed two known interactors of SET, glyceraldehyde-3-phosphate dehydrogenase 50 and T-complex protein 1 subunit delta 51 .…”
Section: Resultsmentioning
confidence: 99%